Influence of time of application of Pseudomonas fluorescens in suppressing sheath blight of rice - A.P. SINHA, RAJBIR SINGH and (Indian Phytopathology, 2005)
The present investigation was undertaken to test the effectivity of potential strains of Pseudomonas fluorescens against sheath blight of rice under field conditions, applied as three time sequences. Foliar sprays with Pfr 1, 7 days before pathogen inoculation resulted in maximum reduction in sheath blight severity (59.6-64.4) and incidence (36.7-40.4), and increasing in grain yield (30.6-32.3) and 1000-grain weight (27.2-29.5). Simultaneous application of the bioagent(s) and R. solani or bioagents applied 7 days after inoculation with R. solani was relatively inferior in reducing the disease.